The Measurement Development of the Almost Perfect Scale-Revised Thai Version for Academically Gifted Students of Mahidol Wittayanusorn School and Kamnoetvidya Science Academy - Nanthasarn, Santipap; Intraprasert, Dusadee; Prayai, Narulmol (Journal of Behavioral Science for Development, 2023)
The Almost Perfect Scale-Revised (APS-R) has been well characterized for assessing Perfectionism in literature. However, no previous studies have evaluated the reliability and validity of the APS-R for academically gifted students in Thailand. Thus, the objective of this study was to develop the APS-R cross-culturally into Thai and evaluate its reliability and validity in a sample of academically gifted students. The APS-R was translated and cross-culturally adapted into Thai according to the international guidelines for the cross-cultural adaptation of self-report measures. The APS-R Thai version was administered to 521 academically gifted students of Mahidol Wittayanusorn School and Kamnoetvidya Science Academy. The results indicated that the APS-R Thai version showed good psychometric properties: internal consistency ( = .72 -.91), convergent (AVE = .35 - .48), and discriminant validity (MSV = .15 - .28). The confirmatory factor analysis revealed that the model was fitted to the empirical data (χ2= 376.7, df = 163, Relative χ2= 2.31, RMSEA = 0.05, CFI =0.99, GFI = 0.94, AGFI=0.90) and the 3-factors model of Perfectionism was confirmed: High standard ( = .77), Order ( = .72), and Discrepancy ( = .91). The Almost perfect scale – revised Thai version demonstrated acceptable acceptability, reliability, and validity; Hence, it can be used in practice and research for assessing Perfectionism in Thai, academically gifted students.